An Assessment of Public Policy Capacity Determiners and Parameters - Humagain, Yadav; Upreti, Bishnu Raj; Devkota, Durga; Mgaya, Yunus D.; Mishra, Rajendra (Nepalese Journal of Agricultural Sciences, 2025)
Policy making is a complex and dynamic process involving various actors and stages, such as formulation, implementation, and evaluation. The effectiveness of public policy depends on the capacity of actors and institutions primarily to formulate, communicate, execute, and assess policies in a comprehensive manner. This study explored the determinants and parameters of policy capacity, identifies critical gaps, such as evidence base, enforcement, and stakeholder engagement. A qualitative approach was used, including literature reviews, field observations, key informant interviews (KIIs), stakeholder consultations, and focus group discussions (FGDs) in five cross reference countries viz. Nepal, India, China, Bhutan and Rwanda. The research identified major key determinants (knowledge, policy skills, political abilities, systemic ability, institutional abilities, leadership skills), and 31 parameters essential for enhancing policy capacity. These findings provide a practical framework to strengthen the capacity of policy actors, ultimately improving the agricultural system and contributing to sustainable development goals through well-informed, evidence-based policy recommendations.